2012
DOI: 10.1016/j.neuropharm.2011.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Review of biological mechanisms and pharmacological treatments of comorbid PTSD and substance use disorder

Abstract: Posttraumatic stress disorder (PTSD) and alcohol/substance use disorder (A/SUD) are frequently comorbid. Comorbidity is associated with poorer psychological, functional, and treatment outcomes than either disorder alone. This review outlines biological mechanisms that are potentially involved in the development and maintenance of comorbid PTSD and A/SUD including neurotransmitter and hypothalamic-pituitary-adrenal dysregulation, structural differences in the brain, and shared genetic risk factors. The literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 96 publications
1
64
1
1
Order By: Relevance
“…Only a few studies have examined the efficacy of specific pharmaceuticals as a stand-alone treatment for concurrent PTSD and SUD, and not one has examined the efficacy of medication in supporting psychotherapeutic interventions. In a recent review of the literature, Norman et al (2011) concluded that medications targeting the serotonin or dopamine system warrant further attention in well-conducted studies with large samples and rigorous scientific methods. Finally, it may also be useful to explore the integration of SUD treatment with intensive, longer term therapy programs such as dialectical behavior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the efficacy of specific pharmaceuticals as a stand-alone treatment for concurrent PTSD and SUD, and not one has examined the efficacy of medication in supporting psychotherapeutic interventions. In a recent review of the literature, Norman et al (2011) concluded that medications targeting the serotonin or dopamine system warrant further attention in well-conducted studies with large samples and rigorous scientific methods. Finally, it may also be useful to explore the integration of SUD treatment with intensive, longer term therapy programs such as dialectical behavior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The high risk hypothesis receives evidence from epidemiological 16 and family genetic studies 17 , and the susceptibility hypothesis mainly from neurobiological and genetic studies 18,19 . The self-medication hypothesis has received support mainly from clinical 20 and epidemiological studies 21--23 .…”
Section: 2shared Pathways Of Trauma and Substance Usementioning
confidence: 99%
“…In several reviews, authors included one or two RCTs in their analyses, and drew most of their conclusions from longitudinal, observational, openlabel, or case studies. 45,51,52 Other reviews included calls for methodological homogeneity and addressed a lack of research on whether different treatments might be more or less effective depending upon etiology, comorbidities, or other patient characteristics. 23,31,32,44,[53][54][55][56] And though individualized treatment is an attractive goal, "To date, no published study has examined the potential for matching treatment protocol based on symptom profile."…”
Section: The Clinical Evidence Basementioning
confidence: 99%